Imagining and Practising Citizenship in Austere Times - John Clarke (Social Work and Society, 2025)
A central issue in the reform of welfare systems concerns the citizenship relationship. Citizenship is critical in three ways: • It has been the focus of political struggles to redraw the boundaries of citizenship: who counts as a citizen? • It has been the focus of reforms seeking to redraw the balance of 'rights and responsibilities' between the state and the citizen, making citizenship more conditional; and • It remains the focus of desires and demands for support and solidarity. Drawing on recent collaborative research with advice agencies (Citizens Advice in the UK), I explore how citizenship is imagined and practiced in different settings - from the policing of nationality to state welfare - contrasting the growing conditionality and exclusiveness of state-centric definitions with alternative imaginaries that celebrate expansive and horizontal forms of identification.